Acrosome integrity assessment of boar spermatozoa images using an early fusion of texture and contour descriptors. Issue 1 (June 2015) - García-Olalla, Oscar; Alegre, Enrique; Fernández-Robles, Laura; Malm, Patrik; Bengtsson, Ewert
<x xml:space="preserve">Abstract</x> Graphical abstract